Formal specification of an object oriented-graphics kernel - Sison, Raymund C. (Animo Repository, 1990)
Most, if not all, computer graphics software packages exhibit two limitations: their highest level of abstraction is procedural, and their specification is informal. Data abstraction and object-orientation lead to the simplification of software development formal specifications result in precise and mathematically verifiable descriptions. This thesis uses an object-oriented approach in the design and implementation of a computer graphics kernel, and a formal (algebraic-axiomatic) approach in the specification and analysis of its properties and behavior. Order-sorted algebras are used to model inheritance. An outline of a correctness proof for a small programming example is given. The synergy of these two approaches to graphical modeling, is finally examined and recommendations are provided for further work.